Slide1.JPG

Slide2.JPG
Slide3.JPG Slide4.JPG Slide5.JPG Slide6.JPG Slide7.JPG Slide8.JPG Slide9.JPG

  1. Chapter 5 Class 12 Continuity and Differentiability
  2. Serial order wise
Ask Download

Transcript

Ex 5.6, 7 If x and y are connected parametrically by the equations without eliminating the parameter, Find 𝑑𝑦/𝑑π‘₯, π‘₯ =(〖𝑠𝑖𝑛〗^3 𝑑)/√(cos⁑2𝑑 ) , 𝑦 = (γ€–π‘π‘œπ‘ γ€—^3 𝑑)/√(cos⁑2𝑑 ) π‘₯ =(〖𝑠𝑖𝑛〗^3 𝑑)/√(cos⁑2𝑑 ) & 𝑦 = (γ€–π‘π‘œπ‘ γ€—^3 𝑑)/√(cos⁑2𝑑 ) 𝑑𝑦/𝑑π‘₯ = 𝑑𝑦/𝑑π‘₯ Γ— 𝑑𝑑/𝑑𝑑 𝑑𝑦/𝑑π‘₯ = 𝑑𝑦/𝑑𝑑 Γ— 𝑑𝑑/𝑑π‘₯ 𝑑𝑦/𝑑π‘₯ = (𝑑𝑦/𝑑𝑑)/(𝑑π‘₯/𝑑𝑑) Calculating π’…π’š/𝒅𝒕 𝑦 = (γ€–π‘π‘œπ‘ γ€—^3 𝑑)/√(cos⁑2𝑑 ) 𝑑𝑦/𝑑𝑑 " " = 𝑑/𝑑𝑑 ((γ€–π‘π‘œπ‘ γ€—^3 𝑑)/√(cos⁑2𝑑 )) Using quotient rule As (𝑒/𝑣)^β€² = (𝑒^β€² 𝑣 βˆ’ 𝑣^β€² 𝑒)/𝑣^2 𝑑𝑦/𝑑𝑑 " " = (𝑑(γ€–π‘π‘œπ‘ γ€—^3 𝑑)/𝑑𝑑 . √(cos⁑2 𝑑) βˆ’ 𝑑(√(cos⁑2𝑑 ))/𝑑𝑑 .γ€– cos^3〗⁑𝑑)/(√(cos⁑2 𝑑))^2 𝑑𝑦/𝑑𝑑 " = " (3 cos^2⁑〖𝑑 γ€—. 𝑑(cos⁑𝑑 )/𝑑𝑑. √(cos⁑2 𝑑) βˆ’ 1/(2√(cos⁑2𝑑 )) . 𝑑(cos⁑2𝑑 )/𝑑𝑑 .γ€– cos^3〗⁑𝑑)/(√(cos⁑2 𝑑))^2 𝑑𝑦/𝑑𝑑 " = " (3 cos^2⁑〖𝑑 γ€—. (βˆ’sin⁑𝑑 ) . √(cos⁑2 𝑑) βˆ’ 1/(2√(cos⁑2𝑑 )) . (βˆ’2 sin⁑2𝑑) .γ€– cos^3〗⁑𝑑)/(√(cos⁑2 𝑑))^2 𝑑𝑦/𝑑𝑑 " =" (βˆ’3 cos^2⁑〖𝑑 γ€— sin⁑𝑑 √(cos⁑2 𝑑) + 1/√(cos⁑2𝑑 ) . sin⁑2𝑑 .γ€– cos^3〗⁑𝑑)/(√(cos⁑2 𝑑))^2 𝑑𝑦/𝑑𝑑 " =" ((βˆ’3 cos^2⁑〖𝑑 γ€— sin⁑𝑑 √(cos⁑2 𝑑) Γ— √(cos⁑2𝑑 ) + sin⁑2𝑑 .γ€– cos^3〗⁑𝑑)/√(cos⁑2𝑑 ))/(√(cos⁑2 𝑑))^2 𝑑𝑦/𝑑𝑑 " =" (βˆ’3 cos^2⁑〖𝑑 γ€— sin⁑𝑑 (cos⁑2 𝑑) + sin⁑2𝑑 .γ€– cos^3〗⁑𝑑)/((√(cos⁑2 𝑑))^2 (√(cos⁑2 𝑑)) ) 𝑑𝑦/𝑑𝑑 " =" ( cos^2⁑𝑑 (βˆ’3 sin⁑𝑑 .cos⁑2𝑑 +γ€– cos〗⁑𝑑 . sin⁑2𝑑 ))/((cos⁑2 𝑑)^(3/2) ) Calculating 𝒅𝒙/𝒅𝒕 π‘₯ = (〖𝑠𝑖𝑛〗^3 𝑑)/√(cos⁑2𝑑 ) 𝑑π‘₯/𝑑𝑑 = 𝑑/𝑑π‘₯ ((〖𝑠𝑖𝑛〗^3 𝑑)/√(cos⁑2𝑑 )) 𝑑π‘₯/𝑑𝑑 = (𝑑(〖𝑠𝑖𝑛〗^3 𝑑)/𝑑𝑑 . √(cos⁑2𝑑 ) βˆ’ (𝑑(√(cos⁑2𝑑 )) )/𝑑π‘₯ . γ€– 𝑠𝑖𝑛〗^3 𝑑 )/(√(cos⁑2𝑑 ))^2 𝑑π‘₯/𝑑𝑑 = (3 〖𝑠𝑖𝑛〗^2 𝑑 . (𝑑(sin⁑𝑑 ) )/𝑑𝑑 . √(cos⁑2𝑑 ) βˆ’ 1/(2√(cos⁑2𝑑 )) . (𝑑(cos⁑2𝑑 ) )/𝑑π‘₯ . γ€– 𝑠𝑖𝑛〗^3 𝑑 )/(√(cos⁑2𝑑 ))^2 𝑑π‘₯/𝑑𝑑 = (3 〖𝑠𝑖𝑛〗^2 𝑑 . cos⁑𝑑 . √(cos⁑〖2 𝑑〗 ) βˆ’ 1/(2√(cos⁑〖2 𝑑〗 )) . (βˆ’sin⁑2𝑑 ) . 2 . γ€– 𝑠𝑖𝑛〗^3 𝑑 )/((cos⁑〖2 𝑑〗 ) ) 𝑑π‘₯/𝑑𝑑 = (3 〖𝑠𝑖𝑛〗^2 𝑑 . cos⁑𝑑 . (√(cos⁑2𝑑 )) . (√(cos⁑2𝑑 )) + sin⁑2𝑑 . γ€– 𝑠𝑖𝑛〗^3 𝑑 )/((√(cos⁑2𝑑 )) (cos⁑2𝑑 ) ) 𝑑π‘₯/𝑑𝑑 = (3 〖𝑠𝑖𝑛〗^2 𝑑 . cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . γ€– 𝑠𝑖𝑛〗^3 𝑑 )/(cos⁑2𝑑 )^(3/2) 𝑑π‘₯/𝑑𝑑 = (〖𝑠𝑖𝑛〗^2 𝑑 (3 cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . sin⁑𝑑 ) )/(cos⁑2𝑑 )^(3/2) Therefore 𝑑𝑦/𝑑π‘₯ = ((cos^2⁑𝑑 (βˆ’3 sin⁑𝑑 .cos⁑2𝑑 +γ€– cos〗⁑𝑑 . sin⁑2𝑑 ))/((cos⁑2 𝑑)^(3/2) ))/((〖𝑠𝑖𝑛〗^2 𝑑 (3 cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . sin⁑𝑑 ) )/(cos⁑2𝑑 )^(3/2) ) 𝑑𝑦/𝑑π‘₯ = (cos^2⁑𝑑 (βˆ’3 sin⁑𝑑 .cos⁑2𝑑 +γ€– cos〗⁑𝑑 . sin⁑2𝑑 ))/(〖𝑠𝑖𝑛〗^2 𝑑 (3 cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . sin⁑𝑑 ) ) 𝑑𝑦/𝑑π‘₯ = (cos^2⁑𝑑 (βˆ’3 sin⁑𝑑 .cos⁑2𝑑 +γ€– cos〗⁑𝑑 . sin⁑2𝑑 ))/(〖𝑠𝑖𝑛〗^2 𝑑 (3 cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . sin⁑𝑑 ) ) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((βˆ’3 sin⁑𝑑 .cos⁑2𝑑 +γ€– cos〗⁑𝑑 . sin⁑2𝑑)/(3 cos⁑𝑑 . cos⁑2𝑑 + sin⁑2𝑑 . sin⁑𝑑 )) Taking common cos⁑2𝑑 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((cos⁑2𝑑 (βˆ’3 sin⁑𝑑 + cos⁑𝑑 sin⁑2𝑑/cos⁑2𝑑 ))/(cos⁑2𝑑 (3 cos⁑〖𝑑 γ€—+sin⁑𝑑 . sin⁑2𝑑/cos⁑2𝑑 ) )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((βˆ’3 sin⁑𝑑 + cos⁑𝑑 sin⁑2𝑑/cos⁑2𝑑 )/(3 cos⁑〖𝑑 γ€—+γ€– sin〗⁑𝑑 . sin⁑2𝑑/cos⁑2𝑑 )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((βˆ’3 sin⁑𝑑 + cos⁑𝑑 tan⁑2𝑑)/(3 cos⁑〖𝑑 γ€—+γ€– sin〗⁑𝑑 . tan⁑2𝑑 )) Taking common cos⁑𝑑 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((cos⁑𝑑 (βˆ’3 sin⁑𝑑/cos⁑𝑑 + tan⁑2𝑑))/(cos⁑𝑑 (3 + sin⁑𝑑/cos⁑𝑑 . tan⁑2𝑑 )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((βˆ’3 tan⁑𝑑 + tan⁑2𝑑)/(3 +γ€– tan〗⁑𝑑 . tan⁑2𝑑 )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((tan⁑2𝑑 βˆ’ 3 tan⁑𝑑)/(3 +γ€– tan〗⁑𝑑 . tan⁑2𝑑 )) Using π‘‘π‘Žπ‘›β‘2πœƒ = (2 π‘‘π‘Žπ‘›β‘πœƒ)/(1 γ€–π‘‘π‘Žπ‘›γ€—^2β‘πœƒ ) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 (((2 tan⁑𝑑)/(1 βˆ’ tan^2⁑𝑑 ) βˆ’ 3 tan⁑𝑑)/(3 + (tan⁑𝑑 ) ((2 tan⁑𝑑)/(1 βˆ’tan^2⁑𝑑 )) )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 (((2 tan⁑𝑑 βˆ’ 3 tan⁑𝑑 (1 βˆ’ tan^2⁑𝑑 ))/((1 βˆ’ tan^2⁑𝑑)))/((3 (1βˆ’ tan^2⁑𝑑 ) + tan⁑𝑑 (2 tan⁑𝑑 ))/((1 βˆ’ tan^2⁑𝑑)))) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((2 tan⁑𝑑 βˆ’3 tan⁑𝑑 (1 βˆ’ tan^2⁑𝑑 ))/(3 (1βˆ’ tan^2⁑𝑑 ) + tan⁑𝑑 (2 tan⁑𝑑 ) )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((2 tan⁑𝑑 βˆ’3 tan⁑𝑑 + 3 tan^3⁑𝑑)/(3 βˆ’ 3 tan^2⁑𝑑 + 2 tan^2⁑𝑑 )) 𝑑𝑦/𝑑π‘₯ = cot^2 𝑑 ((tan⁑𝑑 βˆ’3 tan^3⁑𝑑 ) )/((3 βˆ’tan^2⁑𝑑 ) ) Multiplying cot2 t to numerator 𝑑𝑦/𝑑π‘₯ = (cot^2⁑𝑑 Γ— tan⁑𝑑 βˆ’ 3 cot^2⁑𝑑 tan^3⁑𝑑)/(3 βˆ’tan^2⁑𝑑 ) 𝑑𝑦/𝑑π‘₯ = (1/tan^2⁑𝑑 Γ— tan⁑𝑑 βˆ’ 3 Γ— 1/tan^2⁑𝑑 Γ—tan^3⁑𝑑)/(3 βˆ’tan^2⁑𝑑 ) 𝑑𝑦/𝑑π‘₯ = (1/tan⁑𝑑 .βˆ’ 3 tan⁑𝑑 )/(3 βˆ’ tan^2⁑𝑑 ) 𝑑𝑦/𝑑π‘₯ = ((1 βˆ’3 tan⁑𝑑 (tan⁑〖𝑑)γ€—)/tan⁑𝑑 )/(3 βˆ’ tan^2⁑𝑑 ) 𝑑𝑦/𝑑π‘₯ = (1 βˆ’ 3 tan^2⁑𝑑 )/(tan⁑𝑑 (3 βˆ’ tan^2⁑𝑑 ) ) 𝑑𝑦/𝑑π‘₯ = (1 βˆ’ 3 tan^2⁑𝑑 )/(3 tan⁑𝑑 βˆ’tan^3⁑𝑑 ) 𝑑𝑦/𝑑π‘₯ = 1/(((3 tan⁑𝑑 βˆ’γ€– tanγ€—^3⁑𝑑)/(1 βˆ’3 tan^2⁑𝑑 )) ) 𝐴𝑠 tan⁑3π‘₯=(3 tan⁑π‘₯ βˆ’ tan^3⁑π‘₯)/(1 βˆ’ 3 tan^2⁑π‘₯ ) 𝑑𝑦/𝑑π‘₯ = 1/tan⁑3𝑑 π’…π’š/𝒅𝒙 = π’„π’π’•β‘πŸ‘π’•

About the Author

Davneet Singh's photo - Teacher, Computer Engineer, Marketer
Davneet Singh
Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 8 years. He provides courses for Maths and Science at Teachoo. You can check his NCERT Solutions from Class 6 to 12.